Lotus bioinspired superhydrophobic, self‐cleaning surfaces from hierarchically assembled templates. Issue 8 (20th February 2014) - Ho, Audrey Yoke Yee; Luong Van, Emma; Lim, Chee Tiong; Natarajan, Sriram; Elmouelhi, Noha; Low, Hong Yee; Vyakarnam, Murty; Cooper, Kevin; Rodriguez, Isabel
ABSTRACT The super hydrophobic, self‐cleaning properties of natural species derive from the fine hierarchical topography evolved on their surfaces. Hierarchical architectures which are function‐mimetic of the lotus leaf are here described and created from multi‐scale hierarchical assembled templates. The first level of hierarchy was a micromachined dome structure template and the second level of hierarchy was added by layering a thin nanoporous membrane such as porous anodized alumina or an ion track etch membrane. The assembled templates were nanoimprinted by a single step process on thermoplastic films. The wetting angle of the surfaces reached a value of 160° and the self‐cleaning behavior was observed. The superhydrophobic behavior remained over 1 year after fabrication, which demonstrates the stability of these polymeric self‐cleaning topographies. © 2014 Wiley Periodicals, Inc. J. Polym. Sci. Part B. Polym. Phys. 2014, 52, 603–609